Leaves of grass : the complete 1855 and 1891-92 editions - Whitman, Walt, 1819-1892 (Library of America paperback classics., 2011)
"In 1855, a small volume appeared, self-published by a failed Brooklyn journalist and carpenter : twelve untitled poems and a preface announcing the author's aims. A commercial failure, this book was the first stage of a massive, lifelong enterprise. Six editions and thirty-seven years later, 'Leaves of Grass' had been recognized as one of the central masterworks of world poetry. This Library of America Paperback Classic includes two complete texts : the 1855 first edition and the magnificent culminating edition of 1891-92."--taken from back cover.